Writing & speaking at work : a practical guide for business communication - Bailey, Edward P. (Boston : Prentice Hall, 2011)
The book is concise and easy-to-read text which focuses directly on two crucial communication skill, writing and speaking, especially on how to write executive summary.
Includes index.
uaj 08/05/13, ijb 11/04/2019
Loans
Keywords: Business communication; Business writing; Public speaking